BAYESIAN NETWORK INFERENCE FOR GENETIC REGULATORY NETWORK - SARASWATI (NIM: 23507008); Pembimbing: Dra. Harlili, M.Sc., dan Henny Yusnita Zubir, B.S, M.T, TANTRI
This thesis implements Bayesian network inference technique for genetic regulatory network. Genetic regulatory network depicts regulation between genes inside a cell. A gene regulation shows gene influence to expression level of another gene. These regulations perform cell structure and function altogether.